Hydrophobic and oleophobic modified epoxy resin as well as preparation method and application thereof
By introducing thiolactone-capped fluorinated prepolymer into the epoxy resin and carrying out the thiol-ring-opening reaction, the shortcomings of the epoxy resin coating in terms of oleophobic and hydrophobic properties are solved, and the coating is significantly improved Adhesion and stability improve the product user experience.
Patent Information
- Application Number
- CN202411748771.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
AI Technical Summary
The existing epoxy resin coatings have shortcomings in oleophobic and hydrophobic properties, and their stability and adhesion are poor, which affects the product's user experience.
Thiolactone-terminated fluorinated prepolymer was prepared by free radical polymerization and copolymerization chemical reaction, and the epoxy resin was modified by thiol-ring opening reaction to form a hydrophobic oleophobic modified epoxy resin.
It significantly improves the hydrophobic and oleophobic properties of the epoxy resin coating, enhances the adhesion and stability of the coating, improves the surface touch, and improves the user experience of the product.
Smart Images

Figure CN119431737A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating material preparation, and in particular to a hydrophobic and oleophobic modified epoxy resin and a preparation method and application thereof. Background Art
[0002] A hydrophobic coating is a coating material that can form hydrophobic properties on the surface of an object. It can make the surface of an object super hydrophobic, so that water droplets form a very small contact angle on the surface, thereby improving the water resistance and stain resistance of the object. Self-cleaning coatings represented by transparent hydrophobic and oleophobic surfaces have always been the research focus in the field of surface chemistry. Because they do not require the assistance of detergents and can keep themselves clean only under the action of water, there is a large application demand in the fields of construction, automobiles, decoration, etc.
[0003] The widely used polydimethylsiloxane (PDMS) coating exhibits liquid properties due to the flexibility of the grafted chain, and can repel water-based and oily pollutants. However, the PDMS coating has relatively poor stability, a short coating life, and insufficient adhesion, which is far inferior to epoxy resin. In addition, the larger molecular chain of PDMS makes the surface slippery, affecting the user experience of the product.
[0004] The present invention provides a modified epoxy resin, which can significantly improve the oleophobic and hydrophobic properties of an epoxy resin coating while ensuring light transmittance. Compared with a PDMS coating, the adhesion and stability of the coating are significantly improved, the surface feel of the coating is improved, and the use experience of the product is enhanced. Summary of the invention
[0005] The embodiments of the present application provide a hydrophobic and oleophobic modified epoxy resin and a preparation method and application thereof. The modified epoxy resin of the present invention has a low fluorine content and has excellent hydrophobic and oleophobic properties without affecting the light transmittance. The salt acid resistance and durability of the coating are also improved.
[0006] The embodiment of the present application provides a hydrophobic and oleophobic modified epoxy resin, which is composed of the following components, by mass: 2-5 parts of thiolactone-terminated fluorinated prepolymer, 15-16 parts of 4,4'-diaminodiphenylmethane, 0.13-0.14 parts of base catalyst, 25-26.5 parts of epoxy resin, and the rest is tetrahydrofuran solvent.
[0007] The raw materials of the thiolactone-terminated fluorinated prepolymer are: thiolactone acrylamide, fluoroacrylate and photoinitiator. The fluoroacrylate and the thiolactone acrylamide undergo free radical polymerization and copolymerization chemical reaction under ultraviolet light induction to obtain the thiolactone-terminated fluorinated prepolymer. The mass ratio of the fluoroacrylate, the thiolactone acrylamide and the photoinitiator is: 2~3:1:0.07~0.09.
[0008] The raw materials of the thiolactone acrylamide are: DL-homocysteine thiolactone hydrochloride, NaHCO3 solution and acryloyl chloride, and the mass ratio of the DL-homocysteine thiolactone hydrochloride, the NaHCO3 solution and the acryloyl chloride is: 1:1.3~1.5:1.1~1.3.
[0009] Preferably, the thiolactone-terminated fluorinated prepolymer is preferably 2-4.5 parts.
[0010] Preferably, the epoxy resin is specifically a glycidyl ether epoxy resin, more specifically a trimethylolpropane triglycidyl ether epoxy resin.
[0011] Preferably, the fluoroacrylate is perfluorohexyloctyl acrylate or perfluorooctyl ethyl acrylate, more preferably perfluorooctyl ethyl acrylate.
[0012] The present invention also provides a method for preparing a hydrophobic and oleophobic modified epoxy resin, which is specifically: S1: DL-homocysteine thiolactone hydrochloride, NaHCO3 solution and acryloyl chloride are chemically synthesized in a specific ratio, diluted, extracted and dried to obtain thiolactone acrylamide solid.
[0013] S2: The thiolactone acrylamide prepared in S1 is dissolved in a solvent and purified, and then fluoroacrylate is added, and then a photoinitiator is added. At room temperature, the reaction is stirred under a 400w LED UV lamp to obtain a thiolactone-terminated fluorinated prepolymer solution.
[0014] S3: Dissolve 4,4'-diaminodiphenylmethane in tetrahydrofuran solvent, add the thiolactone-terminated fluorinated prepolymer and base catalyst prepared in S2, stir evenly, then add epoxy resin, stir evenly, and let stand to obtain a clear modified epoxy resin solution.
[0015] Preferably, the solvent in step S2 is one of tetrahydrofuran, acetone, dimethyl sulfoxide or isocyanate silane.
[0016] Preferably, in step S3, the mass ratio of the 4,4'-diaminodiphenylmethane, the thiolactone-terminated fluorinated prepolymer, the base catalyst and the epoxy resin is: 0.4~0.6:0.08~0.16:0.005:1.
[0017] A hydrophobic and oleophobic modified epoxy resin and a preparation method thereof provided in the embodiments of the present application have at least the following technical effects or advantages: 1. A thiolactone-terminated fluorinated prepolymer is obtained by a free radical polymerization copolymerization chemical reaction, and then the epoxy resin is modified and cured by a thiol-ring-opening reaction to prepare an oleophobic and hydrophobic modified epoxy resin, which effectively solves the problem of poor oleophobic and hydrophobic properties of epoxy resin coatings in the prior art, thereby achieving improved oleophobic and hydrophobic properties of the epoxy resin coating, and providing an epoxy resin coating with excellent antifouling properties.
[0018] 2. The glass coating prepared by the thiol-ring-opening reaction modified epoxy resin provided by the present invention has a maximum transmittance of 89% at 550nm, a static contact angle and a contact angle hysteresis of more than 123° and 30° for water, respectively, and a static contact angle and a contact angle hysteresis of 65° and 3° for oily liquids represented by hexadecane, respectively, and has static hydrophobic and excellent dynamic oleophobic effects.
[0019] 3. The present invention provides a method for preparing the thiol-ring-opening reaction modified epoxy resin and a unique ratio between the raw materials for the preparation. The prepared modified epoxy resin coating repels aqueous and oily pollutants and has a self-cleaning function, thereby effectively reducing the maintenance cost of the coating during service.
[0020] 4. The glass coating prepared by the thiol-ring-opening reaction modified epoxy resin provided by the present invention has excellent durability in acid salt solution and still exhibits hydrophobicity and oleophobicity after immersion for 24 hours; after being impacted by high-speed water flow for 15 minutes, the coating still maintains good hydrophobicity and oleophobicity.
[0021] 5. The oleophobic and hydrophobic modified epoxy resin coating provided by the present invention is applied to glass, which not only ensures the light transmittance of the glass, but also significantly improves the hydrophobic and oleophobic properties of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The transmittance of the uncoated original slide and the 6 coated slides with 0 FEOC-0.64 FEOC were tested by UV-visible spectrometer; Figure 2 The average transmittance of the uncoated original slide and the 6 coated slides from 0 FEOC to 0.64 FEOC in the visible light region of 400-760nm; Figure 3 The static contact angles of water and hexadecane for the uncoated original glass slide and the glass slides coated with 6 kinds of coatings ranging from 0 FEOC to 0.64 FEOC; Figure 4 The contact angle hysteresis of water and hexadecane for the 6 coated glass slides ranging from 0 FEOC to 0.64 FEOC; Figure 5 The self-cleaning performance test results of 6 coating surfaces ranging from 0 FEOC to 0.64 FEOC; Figure 6 This is the result diagram of acid salt corrosion resistance of 0.08 FEOC coating; Figure 7 This is the water flow impact test result of 0.08 FEOC coating. DETAILED DESCRIPTION
[0023] The present application provides a hydrophobic and oleophobic modified epoxy resin and a preparation method and application thereof, which solves the problem in the prior art that epoxy resin used as a coating material has weak hydrophilicity and anti-fouling ability.
[0024] The technical solution in the embodiment of the present application is to solve the problem that the above epoxy resin as a coating material has weak hydrophilicity and anti-fouling ability. The overall idea is as follows: First, thiolactone acrylamide is prepared by chemical synthesis, and the thiolactone acrylamide fluoride and acrylate are subjected to free radical polymerization copolymerization chemical reaction under ultraviolet light in a specific ratio to obtain a thiolactone-terminated fluorinated prepolymer, and the thiolactone-terminated fluorinated prepolymer is modified by a thiol-ring-opening reaction in a certain ratio to obtain a modified epoxy resin for curing.
[0025] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Example 1
[0026] S1. To prepare thiolactone acrylamide, 11.42 g (74.3 mmol) of DL-homocysteine thiolactone hydrochloride was dissolved in 200 mL of NaHCO3 solution (16 g NaHCO3, water / dioxane, volume 1:1) and stirred at 0°C for 30 min.
[0027] Then, 12.65 g (139.8 mmol) of acryloyl chloride was added, stirred at room temperature overnight, diluted with 200 mL of saturated brine, extracted with ethyl acetate four times, the organic phase was dried over MgSO4, filtered, and recrystallized to collect the white solid product thiolactone acrylamide.
[0028] S2. Preparation of a thiolactone-terminated fluorinated prepolymer solution. 2.01 g (11.7 mmol) of the thiolactone acrylamide obtained in step S1 was dissolved in 40 g of acetone and purified by filtering with a 0.22 μm filter membrane. 5.18 g (10 mmol) of 1H, 1H, 2H, 2H-heptadecafluorodecyl ester and 0.15 g (0.73 mmol) of 184 photoinitiator were added to the thiolactone acrylamide solution. The mixture was stirred for 30 min, reacted under a 400 W LED UV lamp at room temperature for 30 min, and a thiolactone-terminated fluorinated prepolymer solution with a solid content of 20% was collected.
[0029] S3. Dissolve 0.58 g (2.8 mmol) of 4,4'-diaminodiphenylmethane in 2 g of tetrahydrofuran, then add 0.08 g of the thiolactone-terminated fluorinated prepolymer solution prepared in step S2 and 5 μL of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir at room temperature for 30 min.
[0030] Then, 1 g (3.3 mmol) of trimethylolpropane triglycidyl ether epoxy resin was added to the above mixture and allowed to stand for 30 min to obtain a clear solution. After being scraped on a glass slide, the air-dried coating was cured at 70°C for 30 min and then at 90°C for another 1.5 h to obtain a hydrophobic and oleophobic fluorinated epoxy coating. Example 2
[0031] Except that the amount of the thiolactone-terminated fluorinated prepolymer solution added in step S3 of Example 1 was changed from 0.08 g to 0.16 g, the rest was the same as Example 1. Example 3
[0032] Except that the amount of the thiolactone-terminated fluorinated prepolymer solution added in step S3 of Example 1 was changed from 0.08 g to 0.24 g, the rest was the same as Example 1. Example 4
[0033] Except that the amount of the thiolactone-terminated fluorinated prepolymer solution added in step S3 of Example 1 was changed from 0.08 g to 0.32 g, the rest was the same as Example 1. Example 5
[0034] Except that the amount of the thiolactone-terminated fluorinated prepolymer solution added in step S3 of Example 1 was changed from 0.08 g to 0.64 g, the rest was the same as Example 1. Example 6
[0035] Except that the amount of the thiolactone-terminated fluorinated prepolymer solution added in step S3 of Example 1 was changed from 0.08 g to 0, the rest was the same as Example 1. Example 7
[0036] According to Example 1 to Example 6, 6 coating samples with different numbers, namely 0-FEOC, 0.08-FEOC, 0.16-FEOC, 0.24-FEOC, 0.34-FEOC and 0.64-FEOC, were obtained, and the 6 coating samples with different numbers were tested.
[0037] After the transmittance test by UV-visible spectrometer, the following results were obtained: Figure 1-2The test chart shows that at the wavelength of 550 nm, which is the most sensitive wavelength for human eyes, the transmittance of the uncoated original slide reaches 90.7%, the transmittance of 0-FEOC is 87.6%, and the transmittance of 0.08-FEOC is 89.6%. It can be seen here that 0.08-FEOC has a certain transmittance enhancement effect compared with 0-FEOC. The transmittance of 0.16-FEOC is 84.8%, the transmittance of 0.24-FEOC is 79.1%, and the transmittance of 0.32-FEOC is 77.6%. 0.64-FEOC has been slightly whitened to the naked eye, so the transmittance is significantly reduced to only about 55%.
[0038] The glass slide without solution coating was used as the control group. The data analysis showed that the transmittance of the coating showed an overall downward trend as the fluorine mass ratio increased, especially when the TTFP addition amount increased from 0.32 g to 0.64 g, the average transmittance of the coating dropped sharply from nearly 80% to less than 60%. In the wavelength range of 400-760 nm, the 0.08-FEOC coating showed the best average transmittance, second only to the original glass slide. It can be seen that the transmittance of the 0.08-FEOC coating is the best.
[0039] Using water and hexadecane as probe liquids, the static and dynamic contact angles on six different coating surfaces were measured. The dynamic contact angle is characterized by contact angle hysteresis, which is obtained by slowly increasing and decreasing the droplet volume and calculating the difference between the advancing contact angle and the receding contact angle.
[0040] Combination Figure 3-Figure 4 It was observed that for both the original glass slide and the 0-FEOC glass slide, the static contact angle of water on the surface was less than 90°, and the contact angle of hexadecane on the surface was around 0°, showing hydrophilicity and lipophilicity. The addition of TTFP significantly improved the liquid repellency of the coating. For water, different amounts of TTFP added made the contact angle around 123°, showing hydrophobicity, and the contact angle for hexadecane was also stable at around 65°. Other properties need to be judged in combination with the contact angle hysteresis.
[0041] It was observed that for water, the contact angle hysteresis of the five coatings decreased with the increase of TTFP content, ranging from 37° to 30°. For hexadecane, the contact angle hysteresis was only about 3°, which showed good dynamic oleophobic properties, indicating that the oily liquid would not leave any traces on the coating surface.
[0042] It can be seen that the hydrophobic and oleophobic properties of epoxy resin are enhanced by modifying epoxy resin with thiolactone-terminated fluorinated prepolymer. Example 8
[0043] Please refer to Figure 5In order to characterize the self-cleaning performance of the coating, we used wool debris as a simulated pollutant and sprinkled the debris on the 0.08-FEOC surface tilted at 28 degrees. Use a dropper to squeeze out water drops from the top. It can be seen that when the water droplets pass through the coating surface, they can carry away the hydrophilic wool debris pollutants while sliding down. After the entire self-cleaning process, the pollutants on the coating surface are completely removed without any residual stains. Example 9
[0044] In order to verify the durability of the coating, salt acid corrosion resistance and water flow impact tests were then carried out.
[0045] Combination Figure 6-Figure 7 , for 0.08-FEOC, 1M HCl solution and 1M NaCl solution were immersed for 24 hours. After 24 hours, the coating was taken out and the contact angle was measured. The data are as follows.
[0046] Combination Figure 6 , taking the 0.08-FEOC on the left as the control group, after being soaked in 1M NaCl solution and 1M HCl solution, the static contact angle of the coating to water is still greater than 90°, showing hydrophobic characteristics, while the static contact angle to hexadecane decreases. At the same time, the increase in the dynamic water contact angle and dynamic hexadecane contact angle after soaking in 1M NaCl solution is greater than that after soaking in 1M HCl solution, which shows that the coating has better tolerance to HCl than NaCl.
[0047] The water flow test was conducted at a distance of 10 cm from the tap, with a water flow rate of 76.3 mL / s, impacting the coating surface at a 30° angle. After impacting for 5 min, 10 min, and 15 min, the contact angle test was performed. Figure 7 After the water flow impact test, it was found that after 5 min, 10 min, and 15 min of testing, the static contact angles of water and hexadecane on the coating surface did not change much, and the stability was good. The dynamic contact angles of water and hexadecane showed an upward change, but the change was not significant.
[0048] Overall, the coating still exhibits static hydrophobic and dynamic oleophobic properties in salt water corrosion and water flow impact tests.
[0049] In addition, according to the test results of Examples 7-9, the hydrophobic and oleophobic modified epoxy resin provided by the present invention has super oleophobic and hydrophobic properties, and has improved salt resistance and durability. It can be used on glass products, plastic products and photovoltaic glass, and can significantly improve the anti-fouling performance and stability of glass products, plastic products and photovoltaic glass.
Claims
1. A hydrophobic and oleophobic modified epoxy resin, characterized in that: The composition is composed of the following components by mass: 2-5 parts of thiolactone-terminated fluorinated prepolymer, 15-16 parts of 4,4'-diaminodiphenylmethane, 0.13-0.14 parts of base catalyst, 25-26.5 parts of epoxy resin, and the rest is tetrahydrofuran solvent; The raw materials of the thiolactone-terminated fluorinated prepolymer are: thiolactone acrylamide, fluoroacrylate and photoinitiator. The fluoroacrylate and the thiolactone acrylamide are subjected to a free radical polymerization copolymerization chemical reaction under ultraviolet light induction to obtain the thiolactone-terminated fluorinated prepolymer. The mass ratio of the fluoroacrylate, the thiolactone acrylamide and the photoinitiator is: 2-3:1:0.07-0.09; The raw materials of the thiolactone acrylamide are: DL-homocysteine thiolactone hydrochloride, NaHCO3 solution and acryloyl chloride, and the mass ratio of the DL-homocysteine thiolactone hydrochloride, the NaHCO3 solution and the acryloyl chloride is: 1:1.3~1.5:1.1~1.
3.
2. The method for preparing a hydrophobic and oleophobic modified epoxy resin according to claim 1, characterized in that: The following steps are involved: S1: DL-homocysteine thiolactone hydrochloride, NaHCO3 solution and acryloyl chloride are chemically synthesized in proportion, diluted, extracted and dried to obtain thiolactone acrylamide solid; S2: The thiolactone acrylamide prepared in S1 is dissolved in a solvent, purified, and then fluoroacrylate is added, and then a photoinitiator is added. At room temperature, the reaction is stirred under a 400w LED UV lamp to obtain a thiolactone-terminated fluorinated prepolymer solution; S3: Dissolve 4,4'-diaminodiphenylmethane in tetrahydrofuran solvent, add the thiolactone-terminated fluorinated prepolymer and base catalyst prepared in S2, stir evenly, then add epoxy resin, stir evenly, and let stand to obtain a clear modified epoxy resin solution.
3. The method according to claim 2, characterized in that in, The fluoroacrylate is perfluorohexyloctyl acrylate or perfluorooctyl ethyl acrylate, more preferably perfluorooctyl ethyl acrylate.
4. The method according to claim 2, characterized in that The epoxy resin is specifically a glycidyl ether epoxy resin, and more specifically a trimethylolpropane triglycidyl ether epoxy resin.
5. The method according to claim 2, characterized in that The solvent in step S2 is specifically one of tetrahydrofuran, acetone, dimethyl sulfoxide or isocyanate silane.
6. The method according to claim 2, characterized in that The mass ratio of the 4,4'-diaminodiphenylmethane, the thiolactone-terminated fluorinated prepolymer, the base catalyst and the epoxy resin in step S3 is: 0.4-0.6: 0.08-0.16: 0.005:
1.
7. The method according to claim 1, characterized in that The thiolactone terminated fluorinated prepolymer is preferably 2-4.5 parts.
8. The use of the modified epoxy resin according to any one of claims 1 to 4, characterized in that: Application of the modified epoxy resin in photovoltaic glass or plastic products.
Citation Information
Patent Citations
Preparation method of fluorinated epoxy resin coating and fluorinated epoxy resin coating
CN115785761A
Preparation method of self-cleaning glass coating precursor solution
CN118930733A
Glass or PET surface self-cleaning super-hydrophobic coating and preparation method thereof
CN119039847A
Cited By
High-solid low-viscosity acrylic resin as well as preparation method and application thereof
CN120309817A
High-solid, low-viscosity acrylic resin and its preparation method and application
CN120309817B
Preparation method of hydrophobic and oleophobic photovoltaic glass
CN120398432A
A method for preparing hydrophobic and oleophobic photovoltaic glass
CN120398432B